(untitled) (Eurasian Research Bulletin, 2022)
The article describes in detail the application of the method of using Islamic culture in educating students in the spirit of patriotism. A scientific approach was taken to inculcate patriotism in the psyche of young people by studying historical materials, traveling to historical monuments, holy places. The purpose of the study is to enrich and change the worldview of critical and creative approaches of the student and teacher by introducing an unconventional method to the educational process